The Influence of Operating Cash Flow and Accounting Profit On Stock Returns With Liquidity As A Moderating Variable Islamic Economic Perspective (Case Study of Food and Beverage Sector Manufacturing Companies Listed on the IDX in 2012-2022) - Junaidi, Ahmad; Pratiwi, Dinal Eka; Pratiwi, Anggi Julia (ITB AAS INDONESIA Surakarta, 2024)
This research aims to examine operating cash flow, accounting profits and stock returns with liquidity as a moderating variable in food and beverage sector manufacturing companies listed on them Indonesia Stock Exchange (IDX) during the 2012-2022 period. The population in this study was 33 companies. The sampling technique in this research was purposive sampling and obtained 10 company samples. This research is quantitative research withsecondary data. Data collection methods use library study methods and documentation methods. Thedata analysis technique used is SEM-PLS (Structural Equation Models Part Least) processed using SmartPLS0.3. The results of this research indicate that operating cash flow has no effect on stock returns, accountingprofits have no effect on stock returns. Liquidity cannot moderate the relationship between operating cash flowand stock returns, liquidity cannot moderate the relationship between accounting profits and stock returns.